Measurement of the WZ production cross section in pp collisions at √s=7 and 8 TeV and search for anomalous triple gauge couplings at √s=8 TeV - Khachatryan,V; Sirunyan,AM; Tumasyan,A; Adam,W; Asilar,E; Bergauer,T; Brandstetter,J; Brondolin,E; Dragicevic,M; Ero,J; Flechl,M; Friedl,M; et al. (EUROPEAN PHYSICAL JOURNAL C, 2017)
The WZ production cross section is measured by the CMS experiment at the CERN LHC in proton–proton collision data samples corresponding to integrated luminosities of 4.9fb−1 collected at s√=7TeV, and 19.6fb−1 at s√=8TeV. The measurements are performed using the fully-leptonic WZ decay modes with electrons and muons in the final state. The measured cross sections for 71<mZ<111GeV are σ(pp→WZ; s√=7TeV)=20.14±1.32(stat)±0.38(theo)±1.06(exp)±0.44(lumi)pb and σ(pp→WZ; s√=8TeV)=24.09±0.87(stat)±0.80(theo)±1.40(exp)±0.63(lumi)pb. Differential cross sections with respect to the Z boson pT, the leading jet pT, and the number of jets are obtained using the s√=8TeV data. The results are consistent with standard model predictions and constraints on anomalous triple gauge couplings are obtained.